The Effect of Application Use Mom Check on Antenatal Care (ANC) Visits For Pregnant Women In The Working Area of Martapura 2 Health Center) - Kamila, Reygina Tasya; Rafidah, Rafidah; Daiyah, Isrowiyatun; Hapisah, Hapisah (Midwifery Departement Poltekkes Kemenkes Banjarmasin, 2024)
Pregnancy period which is initially expected to be normal can develop into a pathological pregnancy so that efforts need to be made to improve health services by improving Antenatal Care services according to standards. This study aims to determine the effect of using the Mom Check application on Antenatal Care (ANC) visits in pregnant women in the working area of the Martapura 2 Health Center. This type of research is a pre-experiment method with a one group pre-post test approach, the sample in this study was a total of 30 pregnant women with aterm gestational age, which was taken with the Total Sampling technique. The research time began in April-June 2024. The independent variable in this study is the Mom Check application. The dependent variable is the antenatal care visit of pregnant women. Data collection was done by filling out the Mom Check application and google form and observation through the registration book. Data were analyzed using Wilcoxon test with a significance value of α=0.05. The results showed that there was an influence between the use of the Mom Check application on ANC visits in pregnant women in the Martapura 2 Puskesmas work area (P-value = 0.001). With the promotive efforts in the form of using the Mom Check application given to respondents, it has a positive impact, namely an increase in ANC visit data in the working area of Puskesmas Martapura 2. Therefore, other promotive efforts are needed that can attract the attention and help pregnant women in conducting ANC visits. Keywords: App, ANC, Mom Check